2021
DOI: 10.3390/ijms22010447
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of A bHLH Interaction Motif

Abstract: Intrinsically disordered proteins and regions with their associated short linear motifs play key roles in transcriptional regulation. The disordered MYC-interaction motif (MIM) mediates interactions between MYC and MYB transcription factors in Arabidopsis thaliana that are critical for constitutive and induced glucosinolate (GLS) biosynthesis. GLSs comprise a class of plant defense compounds that evolved in the ancestor of the Brassicales order. We used a diverse set of search strategies to discover additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…No SNP changes are in proximity to the two DNA-binding domains (DBDs; positions 72 to 123, and 126 to 174) but the changes at positions 229 and 231 are near the highly conserved MYC-interaction motif (MIM; [F]LN[R][V]A). The core xLNxxA motif is required for binding with bHLH (basic helix-loop-helix) MYC transcription factors, such as MYC2, MYC3 and MYC4, which are responsible for the interaction of GSL transcription factors with the JA signaling pathway (Millard et al 2021 ). It is therefore likely that the identified ortholog of MYB51 is associated with the regulation, biosynthesis, and metabolism of 4MGB in Eruca .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No SNP changes are in proximity to the two DNA-binding domains (DBDs; positions 72 to 123, and 126 to 174) but the changes at positions 229 and 231 are near the highly conserved MYC-interaction motif (MIM; [F]LN[R][V]A). The core xLNxxA motif is required for binding with bHLH (basic helix-loop-helix) MYC transcription factors, such as MYC2, MYC3 and MYC4, which are responsible for the interaction of GSL transcription factors with the JA signaling pathway (Millard et al 2021 ). It is therefore likely that the identified ortholog of MYB51 is associated with the regulation, biosynthesis, and metabolism of 4MGB in Eruca .…”
Section: Resultsmentioning
confidence: 99%
“…Its proximity to two IGMT gene isoforms also indicates that this is a locus for both transcriptional regulation and synthesis of the compound. MYB51 is known to interact directly with MYC2 via a MIM, which is conserved between all known GSL-regulating MYB transcription factors (Millard et al 2021 ). The presence of a JAZ5 ( TIFY 11A ) gene underlying a separate locus for 4MGB on LG12 indicates that JA signaling may influence concentrations via interaction with MYC2.…”
Section: Discussionmentioning
confidence: 99%
“…Members within this subfamily may act similarly to those found in Panax ginseng, where these factors are involved in regulating phenylpropane biosynthesis [60]. The interaction between MYB and bHLH TFs has been shown to influence various processes, including defense metabolism, anthocyanin biosynthesis, and organ development, such as trichome initiation [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that bHLH-type MYC TFs, participating in crosstalk among JA and other hormones as well as environmental signals, allow the coordinated and rapid regulation of GS genes (Mitreiter and Gigolashvili, 2021). MYC-interaction motif mediates interactions between MYC and MYB TFs in A. thaliana that are critical for constitutive and induced GS biosynthesis (Millard et al, 2021). MYC3/4 act additively with MYC2 to stimulate GS biosynthesis (Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%